2021
DOI: 10.1016/j.heliyon.2021.e07050
|View full text |Cite
|
Sign up to set email alerts
|

Smart parking systems: comprehensive review based on various aspects

Abstract: Parking allocation has become a major problem in modern cities for which numerous smart parking systems (SPS) have been developed. This paper aims to provide comprehensive study, comparison and extensive analysis of SPSs in terms of technological approach, sensors utilized, networking technologies, user interface, computational approaches, and service provided. Moreover, the paper fills up the research gap by providing a clear insight into the suitability of SPSs in various environmental conditions and highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(59 citation statements)
references
References 98 publications
0
56
0
3
Order By: Relevance
“…For systematic research conduction, a well-planned methodology becomes the primary requirement [20]. The methodology followed to conduct this research work is shown in Figure 1.…”
Section: Methodology Of the Papermentioning
confidence: 99%
See 1 more Smart Citation
“…For systematic research conduction, a well-planned methodology becomes the primary requirement [20]. The methodology followed to conduct this research work is shown in Figure 1.…”
Section: Methodology Of the Papermentioning
confidence: 99%
“…At present, 74% of the entire population has access to electricity and reached a per capita generation of about 370 kWh. The government aims to establish an electricity infrastructure that will significantly utilize renewable energy resources to generate electricity before it completely runs out of the limited reserve of fossil fuels [20]. The nation aims to address the devastating outcomes of global warming and be among the countries that effectively participate in offsetting the carbon footprint.…”
mentioning
confidence: 99%
“…The Smart parking system is one of the most important services used to decrease jam traffic and difficulties in finding a parking space within a restricted parking area [4]. This system helps in [11]:…”
Section: Isps System Algorithmmentioning
confidence: 99%
“…Several review articles have been presented in the literature that explore, classify, and discuss the technical aspects of smart parking solutions [16][17][18][19]. This section discusses related smart parking systems from existing studies, obtained by searching using the keywords 'smart parking' and 'IoT parking' in several databases such as ISI Web of Science and Scopus.…”
Section: Related Workmentioning
confidence: 99%